THE THE EFFECT OF POST TSUNAMI HOTEL TAX RECEIVING AND PARKING TAX ON ORIGINAL LOCAL REVENUE (PAD) PANDEGLANG REGENCY PERIOD 2015-2019 - Refi Pratiwi; Tri Wahyudi (LPPM Press STIE Indragiri Rengat, 2021)
The Pandeglang Regency Local Tax Service (BP2D), which is in accordance with its authority as the coordinator of hotel tax collection and parking tax, is one of the Local Revenues. One indicator that reflects the independence and success of a region is the receipt of Original Local Revenue (PAD). The purpose of this study was to determine the effect of hotel tax receipts on Original Local Revenue (PAD), to assess the impact of parking tax receipts on Original Local Revenue (PAD), and to determine the effect of hotel tax receipts and parking taxes simultaneously on Original Local Revenue (PAD). ) at Pandeglang Regency 2015-2019. This research was designed using a quantitative research approach. The data collection technique used was secondary data. The research was conducted at The Pandeglang Regency Local Tax Service Agency (BP2D). The sample of this research is the 2015-2019 Pandeglang Regency budget report. The results of this study are hypothesis 1 there is no effect of hotel tax receipts on Original Local Revenue (PAD), hypothesis 2 there is no effect of parking tax receipts on Original Local Revenue (PAD), and hypothesis 3 does not influence hotel tax receipts and parking taxes simultaneously on Original Local Revenue (PAD) at Pandeglang Regency 2015-2019.